The Impact of Public Knowledge Investments on Enterprises’ Competitiveness – Electronics Industry Case - Prokop Viktor (Academic Conferences and Publishing International Limited Reading, 2015)
Knowledge and its accumulation become key production factors and increasingly determine productivity and growth. Innovation and technological change depend on new economic knowledge more than most other economic activities however innovations do not arise in isolation. Therefore firms have to search beyond their own boundaries, and this result in a rapidly growing number of firms developing a strong competitive position by co-creating new products and services with knowledge institutions, suppliers, customers, other firms and increasingly the creative sector. This fact is even greater in the rapidly-changing area of electronics industry where the share of R&D expenditures in total innovation expenditure across industries having high shares. In the case of the electronics industry, this may be explained by the high share of foreign capital in this sector and thus strong external knowledge links when gaining access to academic knowledge sources helps to plug gaps which are identified in in-house expertise. The research intends to (i) investigate and characterize the issues of the firms in the electronics industry within the Czech Republic through the methods using own multiple regression model; (ii) answer research questions whether (a) the implementation of innovations and increase public spending on innovation; (b) public financial support for innovative activities; (c) the purchase of public universities and R&D centres have an impact on economic growth and competitiveness of enterprises. This analysis is based on data from Eurostat from the Community Innovation Survey between the years 2010 – 2012. The research results will help the increasing allocative efficiency of public investment in R&D to enterprises in the Czech Republic.
Vliv veřejných investic do znalostí na konkurenceschopnost firem - Případová studie elektronického průmyslu v České republice
Keywords: Competitiveness; electronics industry; innovation; knowledge management; public investments; Konkurenceschopnost; elektronický průmysl; inovace; znalostní management; veřejné investice